If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5w + -6 = 60 Reorder the terms: -6 + 5w = 60 Solving -6 + 5w = 60 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 5w = 60 + 6 Combine like terms: -6 + 6 = 0 0 + 5w = 60 + 6 5w = 60 + 6 Combine like terms: 60 + 6 = 66 5w = 66 Divide each side by '5'. w = 13.2 Simplifying w = 13.2
| 18=9x+4-2x | | (3+2x)=0.5x+1 | | 7x+10=4x-16 | | 3X=6-3 | | -19=v/10 | | 3x+3x-7=47 | | 2x[2+(5+2)]= | | ln(9x)=2ln(2x) | | 5(4x-4)-9=31 | | X-4y+15=0 | | -3x+4x-10=15x+1 | | 3n-2m=mn+4 | | X+7x=-24 | | 5y^2+40y=325 | | 5(3x-7)-3(x+2)-19x= | | 3(x-2)+(-3)=4(x+1) | | r(2x+3)=0.5x+1 | | b^2=-2+3b | | 20x+12y=344 | | 2(5z-1)-5(z+9)=2(z+1) | | 18-3x=2+2x | | 9n^2=-1 | | 5(3/2)+3(4/2)= | | 41+a=10 | | 2xy-3y+6=0 | | 3x-5=24+7 | | (3x-18)=105+99 | | 5.4+-9.7= | | 2/3x-1/2=3/4 | | 29n=-377 | | 2(x+3)=4*-3 | | (2x-4)2=36 |